Análise da reciprocidade tarifária no comércio entre o Brasil e os Estados Unidos - Soares, Paulo Vítor Fraga (My University, 2025)
International trade consolidated itself as a strategic instrument of power in the post?World War II era, with the United States assuming economic leadership of the West and, after the Cold War, expanding its global influence. Since Donald Trump's election in 2016, a trade policy grounded in the imposition of additional tariffs on partners justified by claims of a lack of reciprocity has intensified. This study examines tariff reciprocity in Brazil-United States bilateral trade, identifying potential asymmetries in the rates applied to the main items of each country's bilateral basket of imports and exports. It is an applied, descriptive, and quantitative investigation based on documentary analysis of official sources, including Brazil's Ministry of Development, Industry, Trade and Services (MDIC), the Harmonized Tariff Schedule of the United States (HTSUS), and the United States International Trade Commission (USITC). The empirical scope comprises 48 items at the HS6 level, selected for their representativeness in FOB value within bilateral trade. Methodologically, the study conducts a direct comparison of tariff rates by HTS/NCM tariff lines and a qualitative analysis of U.S. official documents, including 2025 executive orders used as analytical scenarios that impose additional duties of +10% and, alternatively, +40% on U.S. imports of Brazilian origin, with sector-specific exceptions. The analysis is restricted to assessing tariff reciprocity and its sectoral asymmetries, thereby informing the debate on the potential effects of these measures on bilateral trade flows. In the pre-tariff scenario, sectoral asymmetries prevail: the United States is more restrictive in agricultural commodities, whereas Brazil is more restrictive in manufactured goods. The +10% layer partially narrows the gap without achieving reciprocity; the +40% layer amplifies it. Even with targeted exceptions, item-level heterogeneity persists, suggesting negotiations focused on product-specific lists rather than across-the-board layers. [resumo fornecido pelo autor]
O comércio internacional consolidou-se como instrumento estratégico de poder no pós-Segunda Guerra Mundial, com os Estados Unidos assumindo a liderança econômica do Ocidente e, após a Guerra Fria, ampliando sua influência global. Desde a eleição de Donald Trump, em 2016, intensificou-se uma política comercial baseada na imposição de tarifas adicionais a parceiros, sob o argumento de ausência de reciprocidade. Este estudo analisa a reciprocidade tarifária no comércio bilateral Brasil-Estados Unidos, identificando possíveis assimetrias nas alíquotas aplicadas aos principais produtos da pauta bilateral (importações e exportações) de cada país. Trata-se de pesquisa aplicada, descritiva e quantitativa, sustentada por análise documental em fontes oficiais como o Ministério do Desenvolvimento, Indústria, Comércio e Serviços (MDIC), a Harmonized Tariff Schedule of the United States (HTSUS) e a United States International Trade Commission (USITC). O recorte empírico considera 48 itens em nível HS6, selecionados pela representatividade em valor FOB no fluxo comercial entre os dois países. Metodologicamente, procede-se à comparação direta de alíquotas por códigos HTS/NCM e à análise qualitativa de documentos oficiais norte-americanos, incluindo ordens executivas de 2025 utilizadas como cenários analíticos que impõem adicionais de +10% e, alternativamente, +40% sobre as importações americanas de origem brasileira, com exceções setoriais. O estudo restringe-se a avaliar a reciprocidade tarifária e suas assimetrias por setor, contribuindo para qualificar o debate sobre os efeitos potenciais dessas medidas nos fluxos comerciais bilaterais. No cenário anterior às tarifas de Trump, prevalecem assimetrias setoriais: os EUA mostram-se mais restritivos em commodities agrícolas, enquanto o Brasil o é em bens manufaturados. O adicional de +10% reduz parcialmente o descompasso sem alcançar reciprocidade; já a adição de +40% o acentua. Mesmo com exceções pontuais, a heterogeneidade por item persiste, sugerindo negociações focadas em listas específicas de produtos, e não em camadas gerais. [resumo fornecido pelo autor]
Keywords: Comércio internacional - Brasil - Estados Unidos; Tarifas alfandegárias; Reciprocidade comercial; Exportação